The generalized Roy model and the cost-benefit analysis of social programs - Philipp Eisenhauer; James J. Heckman; Edward Vytlacil (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
The literature on treatment effects focuses on gross benefits from program participation. We extend this literature by developing conditions under which it is possible to identify parameters measuring the cost and net surplus from program participation. Using the generalized Roy model, we nonparametrically identify the cost, benefit, and net surplus of selection into treatment without requiring the analyst to have direct information on the cost. We apply our methodology to estimate the gross benefit and net surplus of attending college.
urn:nbn:de:bsz:180-madoc-372950
Keywords: I21; C31; C32; 330; Cost-Benefit Analysis; Treatment Effects; Returns and Costs to Education